The Significant Role of the Microfilament System in Tumors - Jiang, Xin; Qin, Yiming; Kun, Liu; Zhou, Yanhong (Frontiers in Oncology, 2021)
Actin is the structural protein of microfilament and usually exists in two forms: monomer and polymer. Among them, monomer actin is a spherical molecule which is composed of a polypeptide chain, also known as spherical actin. The function of actin polymers is to produce actin filaments, so it’s also named fibroactin. Actin cytoskeleton has been considered as an important subcellular filament system along these years. It interacts with numerous relevant proteins and regulatory cells, regulating basic functions from cell division, muscle contraction to cell movement and ensuring tissue integrity. The dynamic reorganization of actin cytoskeleton pushes forward an immense influence on the progression and metastasis of cancer as well. This paper explores the significance of microfilament network and the dynamic changes of its structure and function in the presence of tumor, the formation process about actin system and relevant proteins as target molecules of anticancer drugs, so as to provide support and reference for interlinked cancer treatment research in the future.